Relationship Between Body Condition Score Change During the Prepartum Period and Week Four Milk Yield of Dairy Cows - C. A. Gamarra; A. L. Scanavez; L. G. Mendonça (Kansas Agricultural Experiment Station Research Reports, 2018)
The objectives of the study were to (1) evaluate the association between body condition score (BCS) change in the prepartum period and week four milk yield and (2) explore whether average week four milk yield can be used as an indicator of the percentage of cows having BCS loss before calving at the herd level. Cows that had excessive BCS loss had decreased milk yield in early lactation relative to cows that did not change BCS or had moderate BCS loss in the dry period. Nonetheless, monitoring average week four milk yield does not appear to be a reliable indicator of the percentage of cows that underwent excessive BCS loss in the prepartum period. In conclusion, despite its association with BCS change during the dry period, week four milk yield cannot be used as a reliable parameter to monitor whether cows experience excessive BCS loss before calving.
Keywords: body condition score; prepartum period; postpartum milk production